2021
DOI: 10.1007/s42979-021-00530-x
|View full text |Cite
|
Sign up to set email alerts
|

Fourier’s Quantum Information Processing

Abstract: We demonstrate that quantum information processing (QIP) completely rests on quantum Fourier transform (QFT), and 190 years after his death, the work of Jean-Baptiste Joseph Fourier is more present than ever in one of the most important pillars of physics: QIP. Specifically, this study shows the impact of QFT on the main tool of quantum communication: entanglement, with a particular emphasis on its spectral nature, whose study is completed when entanglement is used in teleportation, and quantum secret sharing.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(28 citation statements)
references
References 62 publications
(178 reference statements)
3
25
0
Order By: Relevance
“…It is evident that if we resort to all the equivalences between gates present in the literature [27,30,31], the Fourier expansion in other scopes outside the quantum entanglement and teleportation becomes obvious. This can be seen in detail in a recent work that links QFT with quantum information processing [36].…”
Section: Quantum Entaglement and Teleportationmentioning
confidence: 99%
“…It is evident that if we resort to all the equivalences between gates present in the literature [27,30,31], the Fourier expansion in other scopes outside the quantum entanglement and teleportation becomes obvious. This can be seen in detail in a recent work that links QFT with quantum information processing [36].…”
Section: Quantum Entaglement and Teleportationmentioning
confidence: 99%
“…[31] Although ibmq_5_yorktown is a machine of considerable decoherence, the percentage errors of (Equation 20) are practically insignificant, which highlights the validity of the equivalence of Figure 5c, that is, the validity of the spectral facet of the entanglement. [68,69] Currently, IBM Q Experience [31] does not allow us to implement Controlled-S directly so this gate was implemented using the equivalent circuits of Figure 12, where…”
Section: Bell State |𝛽 00 ⟩mentioning
confidence: 99%
“…[1] This powerful tool has been consolidated over the years in such critical applications as phase estimation, within the most famous quantum algorithm in the literature, the Shor algorithm. [2] In recent years, it has been shown that QFT is a key piece in the same constitution of quantum entanglement, [3][4][5][6] which is why the latter has two complementary facets, a temporal facet, traditionally known, [1] and another spectral, [3][4][5][6] which will lead to the creation of future algorithms and protocols with higher performance to be used in quantum communications, [7] in general, and quantum cryptography, [8] in particular.…”
Section: Introductionmentioning
confidence: 99%
“…The spectral manifestation of entanglement has been exploited to the limit in previous works in implementations ranging from quantum teleportation, [3][4][5][6] through quantum secret sharing (QSS), [3][4][5][6] to quantum repeaters. [3][4][5][6] These applications have a marked projection on the quantum key distribution (QKD) [9][10][11][12] protocols, although their greatest contribution is expected to happen in the field of the future quantum Internet.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation